PERPUSTAKAAN DAERAH KABUPATEN SINTANG DENGAN PENDEKATAN ARSITEKTUR NEO VERNAKULAR - Khaliesh, Hamdil; Tandyono, Willson; Nurhamsyah, Muhammad (JMARS: Jurnal Mosaik Arsitektur, 2025)
Sintang District, located in West Kalimantan, has the potential to become the provincial capital in the effort to expand the Greater Kapuas Province. In order to accelerate the realization of community welfare, the government of Sintang District seeks to meet the community's need for access to information and knowledge. Currently, Sintang District has one regional library, but based on observations, the existing library experiences several problems that result in less efficient functioning of the library. Therefore, a new construction of the Sintang Regency Regional Library is needed to overcome this problem. The design of this library aims to meet the needs and activities of the community, as well as support the entire process of library activities. The design process begins with data collection, analysis, and synthesis, which then produces pre-design drawings and detailed engineering design. In this design, an in-depth analysis of the cultural and physical context of Sintang Regency is carried out, so that the library design adopts traditional architectural elements. The result of this design is the Sintang Regency Regional Library building which has one building mass with a stage floor, equipped with a Dayak-patterned secondary skin at the front. The library is designed with comfortable reading rooms and supporting facilities, and integrates neo vernacular architectural values. This approach was chosen to create a building that is not only functional as an information center, but also reflects local cultural identity and creates harmony with the surrounding environment.